Preclinical characterisation of gallium-68 labeled ferrichrome siderophore stereoisomers for PET imaging applications - Krasulova, Kristyna; Neuzilova, Barbora; Dvorakova Bendova, Katerina; Novy, Zbynek; Popper, Miroslav; Hajduch, Marian; Petrik, Milos (EJNMMI radiopharmacy and chemistry, 2024)
BACKGROUND: Siderophores are small iron-binding molecules produced by microorganisms to facilitate iron acquisition from the environment. Radiolabelled siderophores offer a promising solution for infection imaging, as they can specifically target the pathophysiological mechanisms of pathogens. Gallium-68 can replace the iron in siderophores, enabling molecular imaging with positron emission tomography (PET). Stereospecific interactions play a crucial role in the recognition of receptors, transporters, and iron utilisation. Furthermore, these interactions have an impact on the host environment, affecting pharmacokinetics and biodistribution. This study examines the influence of siderophore stereoisomerism on imaging properties, with a focus on ferrirubin (FR) and ferrirhodin (FRH), two cis-trans isomeric siderophores of the ferrichrome type. RESULTS: Tested siderophores were labelled with gallium-68 with high radiochemical purity. The resulting complexes differed in their in vitro characteristics. [68Ga]Ga-FRH showed less hydrophilic properties and higher protein binding values than [68Ga]Ga-FR. The stability studies confirmed the high radiochemical stability of both [68Ga]Ga-siderophores in all examined media. Both siderophores were found to be taken up by S. aureus, K. pneumoniae and P. aeruginosa with similar efficacy. The biodistribution tested in normal mice showed rapid renal clearance with low blood pool retention and fast clearance from examined organs for [68Ga]Ga-FR, whereas [68Ga]Ga-FRH showed moderate retention in blood, resulting in slower pharmacokinetics. PET/CT imaging of mice injected with [68Ga]Ga-FR and [68Ga]Ga-FRH confirmed findings from ex vivo biodistribution studies. In a mouse model of S. aureus myositis, both radiolabeled siderophores showed radiotracer accumulation at the site of infection. CONCLUSIONS: The 68Ga-complexes of stereoisomers ferrirubin and ferrirhodin revealed different pharmacokinetic profiles. In vitro uptake was not affected by isomerism. Both compounds had uptake with the same bacterial culture with similar efficacy. PET/CT imaging showed that the [68Ga]Ga-complexes accumulate at the site of S. aureus infection, highlighting the potential of [68Ga]Ga-FR as a promising tool for infection imaging. In contrast, retention of the radioactivity in the blood was observed for [68Ga]Ga-FRH. In conclusion, the stereoisomerism of potential radiotracers should be considered, as even minor structural differences can influence their pharmacokinetics and, consequently, the results of PET imaging.
Keywords: Imaging; Siderophore; Positron emission tomography; Stereoisomers; Infection